Characterization of silicate scale formation: the effect of pH on silicate scale formation: article - Mohd Yazid, Muhammad Farid; Sazali, Rozana Azrina (2019)
One of the challenging situations or problems that engineers nowadays have been encountering in oil and gas industry is the formation of silicate scale. ASP flooding is one of the methods used to improve the oil recovery efficiency. However, this ASP flooding process could produce the silicate scale. The formation of silicate scale could be throughout overall processes, from upstream to downstream process. In ASP flooding, the water injected into the reservoir is at high pH value, injected to displace the remaining oil in the reservoir. As it propagating within the reservoir from the injection well to the production well, it will mix up with the connate water at neutral pH. This mixing of water will vary the pH of water, causing the pH condition inside the reservoir to be reduced. This reduction of pH will encourage the precipitation of silicate scaling. The lower the value of the pH, the higher the rate of the silicate scale formation. The variation of pH will produce different type of morphology. There were two methods, Fourier’s Transformation Infra-Red or FTIR and also X-ray diffraction to analyze and characterize all the six samples, which were are Magnesium and Silica brine. Three samples of this brine with different condition were prepared. The first brine sample was prepared at room temperature, pH 8.5. While the second brine was at room temperature, pH 11. The third was the mixture of brine sample at room temperature, at pH 8.5 and 11-12 respectively, but taken both brine were left 22 hours before record the observation. The forth sample was magnesium silicate, the fifth sample was magnesium hydroxide and the last sample was silicon dioxide. The sample 4,5 and 6 were the pure commercial compound, used as comparison to the prepared brine. From the results obtained, it clearly showed that pH will affect the precipitation significantly. Sample with lower pH value will has higher intensity, sharp peak and also longer diffraction signals distance. Sharp peak obtained from XRD experiment indicates that there is crystal or scale present in the sample while broad peak indicates the sample is amorphous.